Age at menarche and it's relationship with body mass index - Z Khakbazan; Sh Niroomanesh; A Mehran; A Magidi Ahie (Tehran University of Medical Sciences, 2006)
Background & Aim: Menarcheal age is an important indicator of puberty development in girls and is influenced by a wide variety of factors including race, socio-economic status and etc. The relationship between age at menarche with weight, and BMI is controversial. The present study was designed to determine the relationship between age at menarche and BMI. Methods & Materials: This was a cross-sectional study. The sample size was 580 primary and secondary schoolgirls of Tehran/Iran by using cluster sampling. The data was collected by completing questionnaire and measuring height (cm) and weight (kg) by one trained person and analyzed by Pearson and one way ANOVA. Results: 580 schoolgirls participated in this study. The mean menarcheal age was 12/1(1/2), mean weight 45/6 (8/2) kg and the mean BMI was 18/4 (2/4) kg/m2. This result indicated that there were a statically significance difference in mean height (p<0/0001) and mean weight (p<0/006) at different age of menarche and no significance difference in mean of weight. The Pearson test, show linear positive correlation between age of menarche and height but reversed linear correlation between age of menarche and BMI. Conclusion: According to this finding appears menarcheal age has significant correlation with BMI and height. Therefore as menarcheal age decreases, BMI increases.